Farmers’ Outlook on Agricultural Subsidies in Punjab (Indian Journal of Extension Education, 2018)
Agriculture subsidies are given by centre as well as state governments to the farmers. There are two motives behind providing the agricultural subsidies to farmers; firstly to encourage the use of new technology among the farmers and secondly to reduce the cost of production. This study was conducted in order to get an insight into the farmers’ perspective on agricultural subsidies in Punjab. Ninety beneficiary and ninety non-beneficiary farmers were selected from the three agro-climatic zones of Punjab. Majority of the farmers agreed that subsidies help to increase production but at the same time were making the farmers more dependent on the government. The non-beneficiary farmers perceived that subsidies are biased towards large farmers. A significant difference was found in the variables viz. operational land holding, annual income and mass media exposure of the beneficiary and non-beneficiary farmers. Tobit regression analysis showed that farmers’ operational holding, lack of awareness of time of availability of subsidy, delay in release of subsidies and misallocation of the subsidies significantly affected the receipt of subsidy by a farmer. The idea of farm subsidies being counterproductive finds a strong basis in case of Punjab, where these have started posing a threat not only to the exchequer but also to the sustainability of agricultural operations. Thus, a reorientation in the grant of subsidies is clearly the need of the hour, so that its distorting effects are corrected.